Analysis of The Technical Implementation Unit of Simple Rental Flats in Determining the Criteria for Low-Imcome People for Resident of Simple Rental Flats in Api-Api in Bontang - Nisrina Nadifah Nur Rohadhatul Aisy (Faculty of Law, Universitas Negeri Semarang, 2025)
It was found that some residents of Rusunawa Api-Api did not fit the category of Low-Income Communities (MBR). This study aims to determine and analyze the implementation of determining the criteria for low-income people carried out by UPT Rusunawa and to determine and analyze the obstacles of UPT Rusunawa in determining the criteria for low-income people. The research method applied in this research is qualitative by using the type of empirical juridical research whose data collection is carried out by observation, interviews, documentation, and literature study. The results of this study indicate that although the determination of MBR criteria for residents of Rusunawa Api-Api is carried out systematically and procedurally according to applicable regulations by UPT Rusunawa, it is still less effective because the process it does not escape the constraints.